All That I Studied Gave Me a Clearer Goal” Students’ Voice: Project-Based Learning in ESP Course - Krisdianata, Yoannes Yuka; Larasati, Rachelina (ETERNAL (English Teaching Journal), 2025)
English as the main language held an enormous role in the Ecotourism and Hospitality sectors, moreover in preparing students for the working field. This study examines the use of a project-based learning (PBL) approach in an English for Specific Purposes (ESP) course, specifically in an English for Ecotourism and Hospitality Management class for Thai students. It focuses on students’ perceptions during and after the implementation of PBL. Data were collected through interviews, revealing that participants experienced happiness and enjoyment throughout the process. Additionally, they gained greater clarity about their future goals upon completing their projects. The findings suggest that PBL in ESP not only strengthens students’ knowledge and skills but also promotes their mental well-being. The study concludes with implications and recommendations for future research on PBL and ESP.